The Effect of Native Language (Arabic Language) on Learning English Language - Ahlam Dhahir Mohsin Al-Shamarti (Zien Journals, 2022)
The major goal of this contrastive analysis study was to describe the impact of the Arabic sound system on learning English pronunciation. To this end, this study analyzed the sound systems of Arabic and English in detail to find out similarities and differences. As the analysis revealed, there are similarities and differences between the Arabic and English sound systems mainly in terms of the number of vowels and consonants, diphthongs, syllable structure, and intonation. In some cases, such as Arabic consonants that are absent in English, it was found that differences helped learners master English pronunciation. However, there were also a few cases in which irregularities could cause problems for learners.
Keywords: Arabic sound system, Communication, Contrastive analysis, English sound system